Russian Economic Report, No. 35, April 2016 : The Long Journey to Recovery - World Bank Group (World Bank, Washington, DC, 2016)
Russia’s anticipated economic recovery was delayed. In 2015 the Russian economy began its difficult adjustment to the severe global oil-price shock and the imposition of economic sanctions in 2014. The impact of these twin shocks drove Russia’s economy into a deep recession, which reached its nadir in the second quarter of 2015. Following a brief rally early in the year, a further decline in global oil prices in August 2015 derailed an anticipated recovery, and annual real GDP contracted by a total of 3.7 percent. This report series is produced twice a year by World Bank economists in the Macroeconomics and Fiscal Management Global Practice.